2014
DOI: 10.3389/fmars.2014.00064
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide intrusion in seagrasses assessed by stable sulfur isotopes—a synthesis of current results

Abstract: Sulfide intrusion in seagrasses, as assessed by stable sulfur isotope signals, is widespread in all climate zones, where seagrasses are growing. Seagrasses can incorporate substantial amounts of 34 S-depleted sulfide into their tissues with up to 87% of the total sulfur in leaves derived from sedimentary sulfide. Correlations between 34 δ S in leaves, rhizomes, and roots show that sedimentary sulfide is entering through the roots, either in the form of sulfide or sulfate, and translocated to the rhizomes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 63 publications
5
61
0
Order By: Relevance
“…5A). Both indicators of sulfide intrusion that were measured in this mesocosm study (F sulfide and root S 0 ) are similar to values observed in situ for Zostera marina Borum et al, 2013;Holmer and Hasler-Sheetal, 2014), suggesting that similar sulfur dynamics may occur in coastal regions of the North and Baltic Seas.…”
Section: Sulfur Dynamics Oxygen Fluxes and Sulfide Intrusion Of Eelsupporting
confidence: 83%
“…5A). Both indicators of sulfide intrusion that were measured in this mesocosm study (F sulfide and root S 0 ) are similar to values observed in situ for Zostera marina Borum et al, 2013;Holmer and Hasler-Sheetal, 2014), suggesting that similar sulfur dynamics may occur in coastal regions of the North and Baltic Seas.…”
Section: Sulfur Dynamics Oxygen Fluxes and Sulfide Intrusion Of Eelsupporting
confidence: 83%
“…Although this metabolic shift allows the system to recycle organic carbon, it comes at a high cost by generating high amounts of sulfide that is toxic for seagrasses (Koch and Erskine, 2001). Seagrasses are able to tolerate sulfide intrusion by: (i) reoxidized sulfide by oxygen present in the aerenchyma (Pedersen et al, 2004) or in the rhizosphere (van der Heide et al, 2012) or (ii) organic sulfur conversion into thiols (Holmer and Hasler-Sheetal, 2014). If both mechanisms fail and sulfide intrudes into active tissues such as leaves and meristems, seagrasses suffer in performance (Garcias-Bonet et al, 2008;Pulido and Borum, 2010).…”
Section: B Forms and Effects Of Phenotypic Variation B1 Physiologicalmentioning
confidence: 99%
“…If the plant cannot translocate sucrose efficiently to feed the underground organs, it will consume the storage sugars (underground starch) to maintain root growth and nutrient acquisition metabolisms. This re-mobilization of underground starch shifts the plant metabolism from an energy producer to an active consumer and, thus, impairs growth and primary productivity (Holmer and Bondgaard, 2001;Koch and Erskine, 2001;Holmer and Hasler-Sheetal, 2014).…”
Section: B Forms and Effects Of Phenotypic Variation B1 Physiologicalmentioning
confidence: 99%
“…Bacterially-mediated H 2 S oxidation is about 10.000-100.000 times faster than the chemical reaction alone (Jørgensen and Postgate, 1982) and therefore has potential to be of high value for the plants. It has been suggested that H 2 S oxidation also takes place inside the plant (Holmer et al, 2005;Holmer and Hasler-Sheetal, 2014), as seagrass exposed to high sediment H 2 S levels showed internal accumulation of elemental sulfur that is an intermediate in the sulfide oxidation. This process is, however, driven by simple chemical reactions between H 2 S and O 2 and is not mediated by intra-plant enzymes or bacteria (Pedersen et al, 2004) as seen in some marine invertebrates (Grieshaber and Völkel, 1998).…”
Section: Dark O 2 Microdynamics In the Rhizospherementioning
confidence: 99%